Reverse Genetics Demonstrates that Proteolytic Processing of the Ebola Virus Glycoprotein Is Not Essential for Replication in Cell Culture - Neumann, Gabriele (American Society for Microbiology, 2002)
Ebola virus, a prime example of an emerging pathogen, causes fatal hemorrhagic fever in humans and in nonhuman primates. Identification of major determinants of Ebola virus pathogenicity has been hampered by the lack of effective strategies for experimental mutagenesis. Here we exploit a reverse genetics system that allows the generation of Ebola virus from cloned cDNA to engineer a mutant Ebola virus with an altered furin recognition motif in the glycoprotein (GP). When expressed in cells, the GP of the wild type, but not of the mutant, virus was cleaved into GP1 and GP2. Although posttranslational furin-mediated cleavage of GP was thought to be an essential step in Ebola virus infection, generation of a viable mutant Ebola virus lacking a furin recognition motif in the GP cleavage site demonstrates that GP cleavage is not essential for replication of Ebola virus in cell culture.